Monocytosis Is a Biomarker of Severity in Inflammatory Bowel Disease: Analysis of a 6-Year Prospective Natural History Registry. Issue 1 (9th March 2021) - Anderson, Alyce; Cherfane, Cynthia; Click, Benjamin; Ramos-Rivers, Claudia; Koutroubakis, Ioannis E; Hashash, Jana G; Babichenko, Dmitriy; Tang, Gong; Dunn, Michael; Barrie, Arthur; Proksell, Siobhan; Dueker, Jeffrey; et al.
Abstract: Background: Inflammatory bowel disease (IBD) is associated with alterations of the innate and adaptive immune systems. Monocytes respond to inflammation and infection, yet the relationship between monocytosis and IBD severity is not fully understood. We aimed to characterize the prevalence of monocytosis in IBD and the association between monocytosis and disease severity and IBD-related health care utilization. Methods: We used a multiyear, prospectively collected natural history registry to compare patients with IBD with monocytosis to those without monocytosis, among all patients and by disease type. Results: A total of 1290 patients with IBD (64.1% with Crohn disease; 35.9% with ulcerative colitis) were included (mean age 46.4 years; 52.6% female). Monocytosis was found in 399 (30.9%) of patients with IBD (29.3% with Crohn disease; 33.9% with ulcerative colitis). Monocytosis was significantly associated with abnormal C-reactive protein level and erythrocyte sedimentation rate, anemia, worse quality of life, active disease, and increased exposure to biologics (all P < 0.001). Compared with patients without monocytosis, patients with monocytosis had a 3-fold increase in annual financial health care charges (median: 127, 013 vs. 32, 925, P < 0.001) and an increased likelihood of hospitalization (adjusted odds ratio [AOR], 4.5; P < 0.001), IBD-related surgery (AOR, 1.9; P = 0.002), and emergency department (ED) use (AOR, 2.8; P < 0.001). Patients with monocytosis had a shorter time to surgery, hospitalization, and ED visit after stratifying by disease activity (all P < 0.05). Conclusions: Patients with IBD with monocytosis, regardless of disease type, are at increased risk for worse clinical outcomes, hospitalization, surgery, and ED use. Peripheral monocytosis may represent a routinely available biomarker of a distinct subgroup with severe disease.